The problem of unprofitable activity of enterprises in Ukraine - Demchenko, Ivan; Демченко, Іван Володимирович; Демченко, Иван Владимирович; Yatsukh, Olena; Яцух, Олена Олексіївна; Яцух, Елена Алексеевна (My University, 2018)
The subject of the study. A successful economy does not allow the loss of its main component: enterprises in modern conditions. If the companies of the country do not receive anticipated financial results, the entire financial system becomes vulnerable. This article is focused on research of the problem of loss-making enterprises in Ukraine. It should be noted that the negative trend of a significant number of loss-making companies can be traced over a long period of time. The main reasons for Ukrainian producing companies’ unsatisfactory financial results are described in this article. A hierarchy of factors that determine the financial security of enterprises is constructed. Research of dependence operating profitability of businesses from inflation is done on the basis of statistical data. The tendency in the production of industrial output is shown. Methods. The methods used by authors include correlation analysis, comparative analysis, a method of description, interpretation of statistical data, a method of observation. Scope. The main task of the research remains the demonstration of the problem of non-profit activity of Ukrainian enterprises and the allocation of key factors for the containment of economic growth. For this purpose, a study was made of the dynamics of financial results of subjects of entrepreneurial activity. The dependence of profit on operating activities of the economic sector and the rates of inflation of the national economy of Ukraine is presented. Conclusions. National business adapts to the transformation of the economy and, at the same time, overcomes the diversity of threats. Performed analysis showed that enterprises in Ukraine are strongly influenced by internal independent administrative measures factors. The shortage of financial resources and the complexity of attracting additional funds impede the further development of enterprises. However, the size of revenues and costs, and thus the final financial results will depend on the professionalism of company’s management. The problem of increasing insolvency among Ukrainian companies is disclosed in this paper. Profit formation is possible only if one takes into account the role of the state, changes in external and internal demand and maintaining competitiveness. Key directions of financial stabilization and further business development in Ukraine depend on the ability of entities to maintain an acceptable level of their own financial security.
Keywords: financial crisis; entities; development; entrepreneurial sector; financial results; financial security